Pembaruan Aturan Pemidanaan terhadap Pelaku Kekerasan dalam Rumah Tangga pada KUHP Baru: Studi Perspektif Hukum Islam - Heri Siswan; Budi Sastra Panjaitan; Arifuddin Muda Harahap (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Domestic violence (KDRT) is a form of human rights violation that occurs in the domestic space and has a wide impact on the integrity of the family. The reform of the criminal law through Law No. 1 of 2023 concerning the Criminal Code marks a more serious recognition of domestic violence as a criminal act. This article aims to examine the update of the criminal rules against domestic violence perpetrators in the new Criminal Code and examine it from the perspective of Islamic law. Using a normative juridical approach and comparative analysis, this study found that the new Criminal Code has adopted a more progressive approach to victim protection, including in criminal arrangements against perpetrators. On the other hand, Islamic law views domestic violence as a violation of the principles of justice, compassion, and moral responsibility in the family. Criminalization in Islam is preventive and corrective, and emphasizes a just solution, not merely repressive. Therefore, the reform of the national criminal law needs to be harmonized with Islamic values, in order to establish a penal system that is not only legally just, but also ethically and socially.